Using USLE, GIS and remote sensing for the soil loss assessment in the National Park of Theniet El Had, Algeria - Fellah, Sahnoun; Benzater, Benali; Guemou, Laïd; Hachemaoui, Anouar; Benzohra, Mohamed Nadjib; Elouissi, Abdelkader; Hamimed, Abderrahmane (Future Science, 2024)
Soil water erosion is one of the problems that affect the environment, agriculture and social life by threatening several land surfaces. The objective of this study is to use the USLE model, GIS and remote sensing (RS) to estimate the annual rate of soil loss by water erosion in the Theniet El Had National Park (THNP) which belongs to the mountainous ecosystem of Djebel El Meddad, located in the northwest of Algeria. The use of the USLE model takes into account the five factors controlling water erosion, namely: the rain erosivity (R) determined from the annual rainfall data, the soil erodibility (K) developed from soil survey data, the slope lengths (LS) generated by using DEM, the vegetation cover (C) by the use of RS data and erosion control management practices (P) by field trips. The integration of these factors made it possible to establish the quantitative map of the annual rate of soil loss varying between 0.02 and 55.10 (t/ha.year), with an average of around 6.64 (t/ha.year). Five erosion aggressiveness classes are used; very weak, weak, moderate, strong and very strong which represent a rate respectively of 23.70, 44.65, 22.72, 4.41 and 4.52 % of the study area surface. The areas with high and very high erosion rates are located in the north having a very rugged relief and low vegetation cover. This study can be used in the mountainous ecosystems and it will make it possible to set up priority intervention zones to combat the risk of water erosion.